Trend Analysis of Greenhouse Gas Emission Reduction in Bogor District Since 2010 - Elmasari, Ike; Maruapey, Muhammad Husein; Rusliandy (International Journal of Science and Society, 2025)
This research aims to analyze the trend of greenhouse gas emission reduction in Bogor District since the baseline year of 2010, with a focus on the reporting of low carbon development (LCD) actions implemented by the Bogor District Government. This research uses a qualitative approach with documentation study methods and secondary data analysis, taking place in Bogor District. Data was collected from Bogor District's official reporting through the AKSARA application as well as reports from the Regional Development Planning and Research Agency (Bappedalitbang). Data collected included the number of DRR actions, emission measurements, and cumulative greenhouse gas emission reductions from the baseline year to 2025. Data analysis was conducted quantitatively and qualitatively to understand the achievements and effectiveness of low carbon development policies. Trend analysis of GHG emission reduction in Bogor District shows consistent results that during the period 2010-2025, Bogor District succeeded in reducing GHG emissions by 1,644,900 tons CO2eq. The most significant sector with this reduction is the land sector. Challenges faced during the period include the need for more accurate data verification and the involvement of the transportation sector, which is still one of the largest contributors in Bogor District. Recommendations that can be given from this scientific article include strengthening local policies and regulations, increasing the involvement of the transportation sector, and increasing the involvement of the land sector.